Normal values of cerebrovascular reserve capacity after stimulation with acetazolamide measured by xenon 133 single-photon emission CT. - Leinsinger, G; Piepgras, A; Einhäupl, K; Schmiedek, P; Kirsch, C M (American Journal of Neuroradiology, 1994)
PURPOSE To determine whether a standardized stimulation challenge with acetazolamide will be helpful for assessing the vasodilatory capacity in patients with obstructive cerebrovascular disease. METHODS To establish normative data of the cerebrovascular reserve capacity, a group of 41 control patients was investigated. The regional cerebral blood flow was measured quantitatively before and after stimulation with acetazolamide using the xenon 133 inhalation method and dynamic single-photon emission CT. RESULTS A significant increase of regional cerebral blood flow was found after administration of 1 g of acetazolamide. By doubling the dose no significant further increase was measured. We found no correlation of either baseline or stimulated flow values with age. However, a linear dependence between the stimulated flow values and their respective baseline values was observed. CONCLUSION The standardized challenge with acetazolamide seems to be a reliable method to determine cerebrovascular reserve capacity quantitatively.